Caracterización de parásitos gastrointestinales y externos en ovinos (Ovis aries) en tres fincas del municipio de Sotará – Cauca (2021)
Parasitic diseases are a health problem worldwide, affecting the health and well-being of the ovine species, altering the normal productive parameters that affect the growth and development of lambs, thus reducing weight gain and reducing their reproductive performance, which causes economic losses of great impact and importance in the production systems, therefore in 2020 a study was carried out in the municipality of Sotará that aimed to: The characterization of gastrointestinal and external parasites in sheep on three farms in the municipality of Sotará -Cauca. The methodology used was the taking of 60 stool samples directly from the rectum of the animal belonging to the selected population, where the collected samples were analyzed using the McMaster and Flotation chamber tests in order to identify the most frequent endoparasites; In addition, the visual inspection of the entire body surface, extracting the parasite using a forceps without a mouse tooth and collecting it in an appropriate container for the identification of ectoparasites in these specimens, in this way, the results were correlated with age, sex and race , where it was possible to conclude that the most frequent internal parasites were four nematodes Trichostrongylus, Haemonchus, Neoascaris and Cooperia, a cestode: Moniezia and a protozoan: Eimeria and the ectoparasites were the chewing louse Bovicola and the false tick Melophagus.